2010 35th IEEE Photovoltaic Specialists Conference 2010
DOI: 10.1109/pvsc.2010.5614576
|View full text |Cite
|
Sign up to set email alerts
|

Wide-bandgap (AgCu)(InGa)Se<inf>2</inf> absorber layers deposited by three-stage co-evaporation

Abstract: Wide-bandgap (AgCu)(InGa)Se2 absorber layers with Ga/(In+Ga) = 0.8 were deposited by a three-stage coevaporation process using varying Se incident flux and stage-one substrate temperature. Films exhibited preferential (204)/(220) orientation and a Ga-deficient notch near the surface, both characteristics analogous to previously reported Cu(InGa)Se2 films deposited using the same process. Increasing Se-tometals molar flux ratio from Se/M ≈ 5 to Se/M ≈ 20 reduced process variability, but did not result in an ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Silver alloying with CIGS solar cells has several effects: reducing the alloy melt temperature; widening it's bandgap; reducing sub-bandgap disorder, and potentially providing a pathway for wide bandgap solar cells with high efficiency [2], [3], [4]. We previously showed that the addition of Ag changes the composition and bandgap gradients that result from this process [1].…”
Section: Introductionmentioning
confidence: 99%
“…Silver alloying with CIGS solar cells has several effects: reducing the alloy melt temperature; widening it's bandgap; reducing sub-bandgap disorder, and potentially providing a pathway for wide bandgap solar cells with high efficiency [2], [3], [4]. We previously showed that the addition of Ag changes the composition and bandgap gradients that result from this process [1].…”
Section: Introductionmentioning
confidence: 99%
“…Lower melting temperature than its counterpart Cu(In,Ga)Se 2 (CIGS) may produce (Ag,Cu)(In,Ga)Se 2 (ACIGS) absorbers with lower defect densities [2] and provide a potential pathway to absorber materials for wide-bandgap solar cells with high performance. Three-stage coevaporation [3] has been adopted for wide-bandgap ACIGS deposition and has achieved higher open-circuit voltage (V oc ) while maintaining reasonable short-circuit current (J sc ) and fill factor (FF) [4], [5]. In addition, higher growth temperature is also of interest for exploration, as thermal energy can directly affect certain film properties.…”
Section: Introductionmentioning
confidence: 99%
“…While Ag alloying led to reduced solar cell efficiencies for CuInSe 2, 18 several studies reported on efficiency improvements for absorbers with GGI > 0.5, showing that V OC , fill factor (FF), and J SC can potentially be increased. [19][20][21][22] Already in 2005, Ag(In,Ga)Se 2 (AIGS) was identified as a suitable material for wide-gap solar cells, 23 yielding efficiencies of η > 9% (V OC = 949 mV) for a band gap of E g = 1.70 eV. 24 Later, in 2009, an efficiency of 13.0% (V OC = 890 mV) was achieved by using an ACIGS absorber with E g = 1.60 eV ([Ag]/([Ag] + [Cu]) ≡ Ag/I = 0.75 and GGI = 0.8).…”
mentioning
confidence: 99%